Common methods of illegal abortion and the etiologies of maternal deaths due to its practice - M Kazemian (JRI, 2005)
Introduction: Facing dead bodies of mothers due to criminal abortion in the dissecting hall of forensic medicine offices or in hospitals is due to the ignorance of a social reality which has not been addressed well by a decisive action for its solution or control. Unfortunately, eighty thousand maternal deaths occur each year in the world due to criminal abortions which are accompanied by the deaths of 80000 fetuses too. The 10% illegal abortion of all abortions carried out in Iran indi-cates the importance of the subject for consideration. The termination of pregnancy before fetal capability for extra uterine viability without any legal justification is considered criminal abortion. Mothers or inexpert people and sometimes delinquent medical personnel, commit criminal abor-tion, often in unscientific ways. Most cases of criminal abortion are committed during the second or third month of pregnancy by the use of different medications or local injuries, but in the first month it is usually done by blunt traumas to the abdominal or pelvic areas. Common methods of illegal abortion: 1. Abortificant drugs: Low doses of these drugs are ineffective, but in high doses without having any direct abortificant effect, result in abortion by toxifying the mother. 2. Local abortificants: These substances are applied in the vagina or onto the cervix and they will cause abortion by their chemical properties. 3. Instrumentation: These are the most effective methods used and are done via three methods: a) douching b) syringing c) direct instrumentation. Causes of death due to criminal abortions are: a) inhibition deaths or deaths because of overdosing, b) hemorrhagic shock, c) septicemia, d) drug or chemical poisoning, e) air emboli or f) amniotic fluid emboli. Conclusion: Familiarization of physicians and medical personnel with illegal abortions and causes of maternal deaths due to this problem and also an attempt to find a solution for its control or decrease, together with familiarization of authorities in Iran may finally lead to a solution and control of illegal abortions in the society.
Keywords: Criminal abortion, Morality, Autopsy, Abortificant drugs, Law, Toxicity